Early Identification of Olive Oil Defects throughout Shelf Life - Freitas, Flávia (2024)
The unique aroma and flavor of extra virgin olive oil (EVOO) are generally associated with its volatile composition, which includes a variety of components responsible for positive attributes as well as sensory defects which result from chemical oxidation processes and the action of exogenous enzymes. In this study, a robust analytical method, headspace solid-phase microextraction combined with gas chromatography–mass spectrometry (HS-SPME-GC/MS), was developed to tentatively identify volatile organic compounds (VOCs) as markers of positive and negative attributes, correlating them with relative percentages to estimate the risk of disqualification during the shelf life of EVOO. Significant differences (p < 0.05) were identified in the levels of VOCs over time, mainly those derived from the lipoxygenase (LOX) pathway. Principal component analysis (PCA) was applied to process the experimental data. The ratio of E-2-hexenal to acetic acid allowed for the prediction of the disqualification of monovarietal EVOO by the sensory panel.